Edukasi Dan Pelatihan Pengelolaan Sampah Non-Organik Di Kelurahan Meranti Pandak Kecamatan Rumbai Pesisir Kota Pekanbaru - Zuhdi, Sulaiman; Hernimawati, Hernimawati; Dailiati, Surya; Saputra, Trio (LPPM UMRI, 2025)
The problem of non-organic waste in urban areas in Indonesia remains a major challenge, particularly with rapid population growth and increasing consumption patterns. Meranti Pandak Village in Pekanbaru City, located on the banks of the Siak River, is no exception to this problem. Low community awareness and skills in managing non-organic waste are contributing factors. To address this issue, a community service program implemented in Meranti Pandak aims to improve the community's knowledge, skills, and marketing networks, enabling them to process waste into products with economic value. The program ran for four months, from May to August 2025, using an emancipatory, participatory approach that involved residents at every stage, from planning to evaluation. The program's results demonstrated an increase in participants' knowledge and skills, resulting in four marketable product prototypes. Furthermore, the formation of community working groups demonstrates positive collaboration. The program also successfully established partnerships with MSMEs and environmental communities, opening up opportunities for a circular economy while strengthening the program's sustainability